A taxonomic monograph of the genus Solariola Flach, 1908 (Coleoptera: Curculionidae: Entiminae) - Bello’, Cesare; Osella, Giuseppe; Baviera, Cosimo (Zootaxa, 2019)
A revision of the genus Solariola Flach, 1908 of the tribe Peritelini Lacordaire (1863) (Curculionidae: Entiminae) which includes forty-three species is completed. According to morphological characters and distribution, the species are divided into three informal groups (the number of species ascribed to the group is in brackets). These are the Solariola doderoi group (15), the Solariola gestroi group (14) and the Solariola paganettii group (14). We present keys for the identification of the genus among the Palaeartic Peritelini and keys to identify all species groups and species. Distribution maps and data on ecology and phenology are also provided. In addition to the following nine species already belonging to the genus we list 34 new species as well: Solariola gestroi (A. & F. Solari, 1903), Solariola paganettii (Flach, 1905), Solariola doderoi A. & F. Solari (1923), Solariola hirtula (A. & F. Solari,1923), Solariola vitalei A. & F. Solari (1923), Solariola ruffoi Osella & Di Marco (1996), Solariola angelae Baviera (2015), Solariola fraterna Baviera (2015), Solariola pesarinii Baviera (2015); Solariola angelinii Bellò, Osella & Baviera sp.n., Solariola benellii Bellò, Osella & Baviera sp.n., Solariola bucolorum Bellò, Osella & Baviera sp.n., Solariola cajetanibelloi Bellò, Osella & Baviera sp.n., Solariola calida Bellò, Osella & Baviera sp.n., Solariola comata Bellò, Osella & Baviera sp.n., Solariola diottii Bellò, Osella & Baviera sp.n., Solariola fancelloi Bellò, Osella & Baviera sp.n., Solariola forbixi Bellò, Osella & Baviera sp.n., Solariola gratiensis Bellò, Osella & Baviera sp.n., Solariola hyblensis Bellò, Osella & Baviera sp.n., Solariola ientilei Bellò, Osella & Baviera sp.n., Solariola margaritae Bellò, Osella & Baviera sp.n., Solariola mariaeclarae Bellò, Osella & Baviera sp.n., Solariola mariaesilvanae Bellò, Osella & Baviera sp.n., Solariola mariaetheresiae Bellò, Osella & Baviera sp.n., Solariola melonii Bellò, Osella & Baviera sp.n., Solariola nemoralis Bellò, Osella & Baviera sp.n., Solariola normanna Bellò, Osella & Baviera sp.n., Solariola obsoleta Bellò, Osella & Baviera sp.n., Solariola pacei Bellò, Osella & Baviera sp.n., Solariola paulimagrinii Bellò, Osella & Baviera sp.n., Solariola pentaphyllica Bellò, Osella & Baviera sp.n., Solariola petriolii Bellò, Osella & Baviera sp.n., Solariola poggii Bellò, Osella & Baviera sp.n., Solariola raphaelis Bellò, Osella & Baviera sp.n., Solariola rosae Bellò, Osella & Baviera sp.n., Solariola sabellai Bellò, Osella & Baviera sp.n., Solariola saccoi Bellò, Osella & Baviera sp.n., Solariola sbordonii Bellò, Osella & Baviera sp.n., Solariola selinusia Bellò, Osella & Baviera sp.n., Solariola tedeschii Bellò, Osella & Baviera sp.n., Solariola venusta Bellò, Osella & Baviera sp.n., Solariola zoiai Bellò, Osella & Baviera sp.n..